A study into the right to sex education in Malaysia primary school: a comparative study / Sri Kartika D.P. Bali and Nurul Arni Annas Goh - D.P. Bali, Sri Kartika; Annas Goh, Nurul Arni (2011)
Sex education should be thought in school in our country. Nearly one million women under the age of 20 get pregnant each year. That means 2800 women get pregnant each day. These women were those who are not even ready to gave birth or take care of their own baby as there are still babies to their parents. If students are educated about the effects sex has on their lives, it lessens their chance of having children at an early age. Knowledge about sex can also lessen the chance of kids receiving sexually transmitted diseases (STDs). First of all, the main reason children have sex prematurely is because they are curious. Students lack knowledge about sex because they haven't been taught about it, however, when children know the consequences behind their actions and the risks they are taking they less likely to want to have sex. If we take the time to show kids what it is like to take care of a child as a teenager or show them AIDS victims; they may be much less likely to want to indulge in sexual activities. Sex education probably can't prevent teenage sex, but it can ensure students have the knowledge they need so they'll be aware of what they are getting themselves into. These are the reasons of us doing this research proposal. It is about time the children in Malaysia to be educating on sex education so that they know what the situations they ar§ facing are and about to face.